Step by step management of male infertility - Pandya, Manish R.; Shah, Sudhir R.; Mehta, Jayant G. (New Delhi, India : Jaypee Brothers Medical Publishers, 2008)
Infertility is simply inability to conceive by a couple inspite of regular normal coitus by the couple involved. Management of mail infertility plays a key part in the practice of total infertility management. This book informs about assessing an infertile couple both by a gynecologist and an andrologist to diagnose accurately for treatment. Informs about development of in vitro fertilization technique to treat both male and female infertility.
1. Sperm Production 2. History and Investigation Taking 3. History of Male Infertility 4. The Basic Semen Analysis 5. Male Factors - Infertility and Ejaculatory Duct 6. Medical Approach for Male Infertility 7. Surgical Approach for Male Infertility 8. Newer Drug 9. Artificial Insemination and IUI 10. Assisted Reproductive Technology (ART) Index
Incluye contenido
Incluye índice
Keywords: INFERTILITY; INFERTILIDAD; SEMEN ANALYSIS; ARTIFICIAL INSEMINATION